THE ANALYSIS OF ERROR ON SOLVING GEOMETRY PROBLEM OF STUDENT AT CLASS IX JUNIOR HIGH SCHOOL ON TAMPAN SUBDISTRICT PEKANBARU - Solfitri, Titi; Roza, Yenita (Proceeding 7th International Seminar on Regional Education, 2015)
Abstrak The weakness of mathematics ability of students can be observed from material mastery of students. The studentâs error on solving the problem is one of the clues to find out the material mastery of students. Therefore, that errors need to be identified to find the influence factors to get the solution. This study was implemented on Junior High School in Tampan Sub district which involve 3 schools, such as SMP 8, SMP 20, SMP 21 and the students of class IX. The purpose of this study were (1) Observing the kind of errors which were done by students on solving similarity problem (2) Observing the factors which caused the studentâs error on solving similarity problem. Based on the data analysis, interview and investigation, it can be concluded that students had concept error, procedure error and carelessness error. The factors which caused the studentâs error were lacking of effort on solving problems, lacking of mastery on the material, less of carefulness on solving problems, lacking of mastery on the prerequisite material and the students did not understand the steps on solving problem. Keywords: Analysis of Error, Similarity, Concept Error, Procedure Error.